2007
DOI: 10.1128/iai.00828-07
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Protein and Viral Vaccines Induces Potent Cellular and Humoral Immune Responses and Enhanced Protection from Murine Malaria Challenge

Abstract: The search for an efficacious vaccine against malaria is ongoing, and it is now widely believed that to confer protection a vaccine must induce very strong cellular and humoral immunity concurrently. We studied the immune response in mice immunized with the recombinant viral vaccines fowlpox strain FP9 and modified virus Ankara (MVA), a protein vaccine (CV-1866), or a combination of the two; all vaccines express parts of the same preerythrocytic malaria antigen, the Plasmodium berghei circumsporozoite protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…Moreover, the trial indicated that although the peptide mixture as formulated did not appear to produce any synergism on immune responses, we expect an additive effect of cell-mediated immunity and antibodies, especially on their blocking activity on sporozoite invasion, which may be more effective than vaccination with individual peptides. [43][44][45] The peptide mixtures induced antibody titers to each peptide that were similar to those from our previous trial, in which volunteers were immunized with single peptides. This suggests that there is no detectable interference in the peptide mixture.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, the trial indicated that although the peptide mixture as formulated did not appear to produce any synergism on immune responses, we expect an additive effect of cell-mediated immunity and antibodies, especially on their blocking activity on sporozoite invasion, which may be more effective than vaccination with individual peptides. [43][44][45] The peptide mixtures induced antibody titers to each peptide that were similar to those from our previous trial, in which volunteers were immunized with single peptides. This suggests that there is no detectable interference in the peptide mixture.…”
Section: Discussionsupporting
confidence: 52%
“…We recently assessed in a pre-clinical P. berghei model in mice whether combined use of a protein-adjuvant based anti-sporozoite vaccine could add to the partial efficacy of a vectored vaccine against the liver-stage parasite. 46 The results were striking (Fig. 2).…”
Section: Towards Higher Efficacy: Combination Approachesmentioning
confidence: 67%
“…Immunological analysis showed that the combination induced both the antibody response induced by the protein-adjuvant vaccine plus the T-cell response induced by the vectors. 46 Hence it appears that there can be synergistic efficacy with this approach, probably resulting from a substantial reduction in sporozoite number effected by the antibodies making it much easier for the T cells to clear a far smaller number of infected liver cells. Data of this type make a compelling case for assessing RTS,S and TRAP vectors together in humans.…”
Section: Towards Higher Efficacy: Combination Approachesmentioning
confidence: 99%
“…These murine studies also described further possible advantages of viral vectors in achieving consistent Ab priming, enhanced Ab avidity, and Th1-type IgG isotype skew. Data from the HIV-1 (32-36) and liver-stage malaria vaccine fields (37,38) also encourage efforts to combine adenoviral-vectored vaccines with protein vaccines.…”
mentioning
confidence: 99%